(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Punica granatum Linn. is a well-known nature power fruit rich in natural bioactive constituents, edible phytoestrogen like substances and other nutritional elements, grown all over the world from Iran to Mediterranean region and Central Asia. It is also described in Ayurveda as Dadim for treating Amlapitta, Raktapitta and used as Hridya and Atisaraghna. It is used for its good nutritive values generally used in the form of Avaleha, Swaras or Juices and Jellies. Several studies conducted previously showed that pomegranate exhibits antibacterial and antifungal activity. Description of pomegranate is being found since Vedic period. Pomegranate is mentioned in Rigveda also. Aacharya sushrut described pomegranate or Dadim (Sanskrit name) as a best fruit i.e. Shrestha under Phalavarga. According to Acharya Vagbhata, Dadim is also included in Shramghna and Hrudya Gana. In various studies in human and rodent models, pomegranate juice has been found to wield antiatherogenic, antioxidant, anti-carcinogenic, and anti-inflammatory, antidiabetic, gastroprotective, hepatoprotective and nephroprotective activities. Several studies on the antioxidant, anti-carcinogenic, and anti-inflammatory and many more potential properties of various parts of pomegranate and its constituents have been already published. Many studies had proved the latent efficacy of pomegranate and its applications including male infertility, Alzheimer’s disease, and obesity. So, the present study aims to discuss the collective information on pomegranate which can provide a summary to study the diverse array of biological actions of pomegranate and thus provide easy accessibility for treating various common diseases.